2018
DOI: 10.20885/jkki.vol9.iss1.art9
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Inflammatory Activities of Ethanolic Extract Elephantopus Scaber Leaves

Abstract: Background: Inflammation is a protective physiological response to tissue injury that can be caused by harmful stimuli. If the inflammatory process is prolonged and cannot restore to homeostatic conditions, this may lead to pathological effects that can damage cells and cause various diseases. Elephantopus scaber is a plant that can easily be found in Indonesia. Elephantopus scaber is a type of plant that is often used as a traditional medicines. Several studies have shown that the compound bioactive content c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Gmelina arborea [ 83 , 84 ], Elephantopus scaber [ 85 , 86 ], and Duhaldea cappa [ 87 ], were also used for their anti-inflammatory properties. For instance, Gmelina arborea [ 84 ] and Elephantopus scaber [ 85 , 86 ] have flavonoids, tannins, and saponins. Miliusa thorelii and Pothos scandens have been used for curing many MSD categories in this study, such as fractures, joint symptoms, and muscle pains, but any phytochemicals that could affect MSD remain to be documented in these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gmelina arborea [ 83 , 84 ], Elephantopus scaber [ 85 , 86 ], and Duhaldea cappa [ 87 ], were also used for their anti-inflammatory properties. For instance, Gmelina arborea [ 84 ] and Elephantopus scaber [ 85 , 86 ] have flavonoids, tannins, and saponins. Miliusa thorelii and Pothos scandens have been used for curing many MSD categories in this study, such as fractures, joint symptoms, and muscle pains, but any phytochemicals that could affect MSD remain to be documented in these species.…”
Section: Discussionmentioning
confidence: 99%
“…Gmelina arborea [83,84], Elephantopus scaber [85,86], and Duhaldea cappa [87], were also used for their anti-inflammatory properties. For instance, Gmelina arborea [84] and Elephantopus scaber [85,86] have flavonoids, tannins, and saponins.…”
Section: Most Preferred Species For Treating Msdmentioning
confidence: 99%
“…Inflammation is a protective physiological response of living tissues to injury (Chou, 1997; Nurtamin et al., 2018; Rajendran et al., 2013). The characteristics of inflammation are heat, swelling, redness, and pain (George, 2006; Prakash, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Elephantopus scaber L. is a type of plant that can be easily found in Indonesia (Nurtamin et al 2018). This plant is also potentially used as a traditional medicine to treat influenza, headaches, cough, fever, diarrhea, jaundice, hepatitis, laryngitis, anemia, and fluor albus (Arisandi & Andriani 2006;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, showed that E. scaber L. can reduce LDL (Low Density Lipoprotein) level and also promising hepatoprotection activity in mice (Daisy et al 2007;Ho et al 2012;Nasri 2012;Puspita 2004;Sankar et al 2001;Sulastri 2008). The leaves of E. scaber L. containing terpenoids, flavonoids, saponins, and tannins which function as antibacterial and antiinflammatory (Bigham et al 2003;Grayson 2000;Lim et al 2006;Nurtamin et al 2018).…”
Section: Introductionmentioning
confidence: 99%